External Conflict and Manipulation Strategy of Ardyn Izunia in Kingsglaive: Final Fantasy XV - Khusnul Rohima (Indonesian Journal of Innovation Multidisipliner Research, 2026)
Conflict is a fundamental element in literary works and films because it drives the plot, shapes character development, and reveals the motivations behind the actions of each character. This study aims to analyze the external conflicts and manipulation strategies employed by Ardyn Izunia in the film Kingsglaive: Final Fantasy XV (2016). It specifically examines how Ardyn creates, controls, and escalates conflicts through his interactions, decisions, and political influence throughout the narrative. This study employs a qualitative descriptive method with a library research design. The data were collected from the film's dialogues, scenes, character actions, and narrative events related to Ardyn Izunia. The analysis applies the concepts of external conflict and characterization theory to identify the forms of conflict experienced by the characters and to explain how Ardyn's personality and behavior contribute to the development of those conflicts. The findings reveal that Ardyn serves as the primary source of political and military conflict between the Kingdom of Lucis and the Niflheim Empire. He employs manipulation, diplomacy, deception, and psychological influence as his principal strategies to achieve his objectives and maintain control over the course of events. Through careful planning, strategic intelligence, and the exploitation of his opponents' weaknesses, Ardyn successfully intensifies the conflict. This study concludes that Ardyn is the central driving force behind the escalation of external conflict, representing a form of power exercised through strategic intelligence, political manipulation, and psychological influence rather than physical strength alone.